Post-surgical sequelae–anal stenosis managed with V-Y advancement flap: a case report - Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Ananthappan, Manoj; Nisa, Jawharun; Jayachandiran, Anand Prasath; Rajendran, Suresh (International Surgery Journal, 2025)
Anal stenosis is a dreaded complication following anal and rectal surgery with moderate and severe cases requiring surgery. Surgery could be anorectal lesions like haemorrhoids, fistulas, fissures or due to post oncological excision and radiotherapy. There is a morbidity associated with primary perineal closure due to multiple wound break downs, delayed recovery from surgery and adjuvant therapies. Herewith, we present our case of a post-oncologic status managed with V-Y gluteal advancement fasciocutaneous flap. This is a safe and simple method with a low complication rate which can relieve the symptoms of anal stenosis.